Are there differences between monochorionic twin placentas after spontaneous and assisted conception?. (August 2022) - Van Lierde, Anette; Delagrange, Hannelore; Russo, Francesca Maria; Van der Merwe, Johannes; Devlieger, Roland; Lewi, Liesbeth
Abstract: Introduction: No data are available on the placental characteristics of monochorionic twin pregnancies conceived by in vitro fertilization (IVF). This study investigates the differences between placentas from monochorionic diamniotic (MCDA) twin pregnancies conceived spontaneously and those conceived after IVF. Methods: This is a retrospective analysis of placental data from a consecutive series of MCDA twin pregnancies followed from the first trimester. The following placental characteristics were compared between IVF versus spontaneous MCDA pregnancies: placental sharing and birth weight discordance relative to placental sharing, the placental angioarchitecture (number, type, and size of anastomoses), and the umbilical cord insertion types. Results: Of the 256 MCDA placentas included in this analysis, 32 (12%) were conceived through IVF and 224 (88%) spontaneously. MCDA twin placentas after IVF did not differ significantly from MCDA twin placentas after spontaneous conception regarding placental sharing, birthweight discordance relative to sharing discordance, and angioarchitecture. There was a trend toward more discordant cord insertions (combination eccentric and velamentous) in IVF (25%) than in spontaneously conceived placentas (12%) (P = 0.05). Discussion: No differences could be demonstrated between MCDA placentation after spontaneous conception and IVF. Any differences in pregnancy outcome between spontaneous and IVF conceived MCDA twins may not be related to differences in placental sharing, angioarchitecture and cord insertion type. Highlights: Spontaneous and IVF conceived monochorionic placentas do not differ significantly in sharing, angioarchitecture and cord insertion. A trend toward more placentas with the combination of an eccentric and velamentous insertion was observed after IVF. Differences in outcome between spontaneous and IVF monochorionic pregnancies may not be related to placental characteristics.